PRMT5 Interacting Partners and Substrates in Oligodendrocyte Lineage Cells - Dansu, David K.; Liang, Jialiang; Selcen, Ipek; Zheng, Haiyan; Moore, Dirk F.; Casaccia, Patrizia (Frontiers in Cellular Neuroscience, 2022)
The protein arginine methyl transferase PRMT5 is an enzyme expressed in oligodendrocyte lineage cells and responsible for the symmetric methylation of arginine residues on histone tails. Previous work from our laboratory identified PRMT5 as critical for myelination, due to its transcriptional regulation of genes involved in survival and early stages of differentiation. However, besides its nuclear localization, PRMT5 is found at high levels in the cytoplasm of several cell types, including oligodendrocyte progenitor cells (OPCs) and yet, its interacting partners in this lineage, remain elusive. By using mass spectrometry on protein eluates from extracts generated from primary oligodendrocyte lineage cells and immunoprecipitated with PRMT5 antibodies, we identified 1196 proteins as PRMT5 interacting partners. These proteins were related to molecular functions such as RNA binding, ribosomal structure, cadherin and actin binding, nucleotide and protein binding, and GTP and GTPase activity. We then investigated PRMT5 substrates using iTRAQ-based proteomics on cytosolic and nuclear protein extracts from CRISPR-PRMT5 knockdown immortalized oligodendrocyte progenitors compared to CRISPR-EGFP controls. This analysis identified a similar number of peptides in the two subcellular fractions and a total number of 57 proteins with statistically decreased symmetric methylation of arginine residues in the CRISPR-PRMT5 knockdown compared to control. Several PRMT5 substrates were in common with cancer cell lines and related to RNA processing, splicing and transcription. In addition, we detected ten oligodendrocyte lineage specific substrates, corresponding to proteins with high expression levels in neural tissue. They included: PRC2C, a proline-rich protein involved in methyl-RNA binding, HNRPD an RNA binding protein involved in regulation of RNA stability, nuclear proteins involved in transcription and other proteins related to migration and actin cytoskeleton. Together, these results highlight a cell-specific role of PRMT5 in OPC in regulating several other cellular processes, besides RNA splicing and metabolism.